Hadith Controversy About Music (Study of Ibn Ḥazm and al-Mubārakfūrī’s Understanding) - Fadhli, Rama (Yayasan Albahriah Jamiah Indonesia, 2025)
Recently, scholars have been discussing a range of issues, including differences of opinion on the law concerning music consumption. This research aims to determine Ibn Ḥazm and al-Mubarakfuri's understanding of music through qualitative methods with descriptive-comparative data analysis techniques. The research findings indicate that Ibn Ḥazm challenges the hadith relied upon by scholars to prohibit music as weak, including those found in the works of al-Bukhārī. According to Ibn Ḥazm, the permissibility of music depends on whether it involves any immorality. On the other hand, al-Mubārakfūrī asserts that music is unequivocally forbidden, although he occasionally permits it under certain circumstances. It is important to note that the differences of opinion among scholars on this issue do not allow for personal preference based on the arguments of each side, as there is a hadith that nullifies one of the positions. In one case, Ibn Ḥazm’s assertion regarding a weak hadith was later confirmed to be authentic, as agreed upon by scholars. Al-Mubārakfūrī maintains that music and musical instruments are impermissible without exception, despite his occasional permission for them.